Association of PTEN Gene SNPs rs2299939 With PFS in Patients With Small Cell Lung Cancer Treated With Early Radiotherapy - Wang, Chunbo; Yang, Depeng; Zhang, Xiaoqing; Zhang, Xiaohan; Yang, Lijun; Wang, Pingping; Zhou, Wenyang; Li, Huaxin; Li, Yiqun; Nie, Huan; Li, Yu (Frontiers in Genetics, 2020)
Lung cancer has higher morbidity and mortality than most cancers. It is common that there are some phenomenons of secondary drug resistance, radiotherapy resistance and poor prognosis during the treatment of small cell lung cancer (SCLC). Recent studies revealed that the single-nucleotide polymorphisms (SNPs) are associated with the curative effect among patients with the same pathological type and stage. Our study analyzed the start time of radiotherapy and the relationship between PTEN gene rs2299939 polymorphisms and survival time among 116 SCLC patients. The results showed that early radiotherapy significantly improved the time of survival in patients compared with late radiotherapy (P = 0.029). Simultaneously, the study found that patients with the rs2299939 AA genotype showed significant sensitivity to both early and late radiotherapy, but early radiotherapy is better. The median survival time of CC genotype patients was 12 months in the early radiotherapy group while it was 9 months in the late radiotherapy group, thus recommending early radiotherapy among these patients. In addition, it was found that rs2299939 could regulate the expression of related genes in peripheral blood and lung tissues by eQTL analysis. This study revealed that the early radiotherapy could prolong the PFS of SCLC and shall be performed in SCLC treatment.